Molecular engineering of the salicylate-inducible transcription factor Sal7AR for orthogonal and high gene expression in Escherichia coli. - Kentaro Miyazaki (PLoS ONE, 2018)
I have previously identified a metagenomic fragment (~4 kb) containing the salicylate (2-hydroxybenzoate)-responsive transcriptional regulator Sal7AR. Taking advantage of the inert nature of salicylate to common genetic switches used in Escherichia coli, here I developed a salicylate-inducible high expression system in E. coli. I first applied a deletion analysis to the metagenomic fragment to identify the core region (~1 kb) necessary for the salicylate-dependent expression. Sal7AR was subjected to an error-prone PCR, and a library was screened for an enhanced expression of a reporter green fluorescent protein (GFP) gene in the presence of 1 mM salicylate, where virtually no growth inhibition was observed. Three beneficial amino acid substitutions were identified (N282K, Q292R, and V295G), each of which improved the expression of GFP relative to the wildtype by several-fold. The three sites were then completely randomized by saturation mutagenesis either individually or combinatorially to identify three variants carrying a single point mutation, N282L, V295F, or V295S; no further improvements were observed by combining these mutations. Salicylate-dependent expression of these mutants was highly repressed in its absence and escalated in response to ~10 μM salicylate, and gradually increased up to 1 mM salicylate; the induction rate was approximately 15 times greater than that achieved with a lactose promoter. Orthogonality to the lactose-based expression system was also confirmed. This salicylate-based expression system should thus be advantageously used for high-level production of recombinant proteins in combination with common lactose-dependent induction systems.